2016
DOI: 10.1080/10426914.2016.1198032
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Preparation Process for Magnetorheological Fluid with High Sedimentation Stability

Abstract: We report the preparation of a high-performance magnetorheological fluid by using silane coupling agent and bentonite as additives at appropriate contents determined by a series of experiments. We also adopted a new preparation process that was optimized through an orthogonal experimental design. The effects of process parameters on the sedimentation stability of the MR fluid were determined. Sedimentation ratio, apparent viscosity, and yield stress were measured to evaluate the performance of the MR fluid pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The authors observed that on‐state viscosity and τ y of MRFs mainly depended on Fe concentration and type of carrier fluid, whereas the other parameters did not contribute significantly. The authors showed that 32 vol% of 300 mesh Fe dispersed in Mi with 0.5 vol% of OA and 0.7 vol% of TMAH gave an optimized MRF with a τ y of 48.07 kPa (experimentally) and 48.197 kPa (theoretically) at 1 T. A similar approach of using orthogonal array was used by Zuzhi et al, [ 79 ] finding that low stirring temperatures, high stirring speeds, and a short first stirring time before a long second stirring time increased sedimentation stability.…”
Section: Ci‐based Mrfsmentioning
confidence: 96%
“…The authors observed that on‐state viscosity and τ y of MRFs mainly depended on Fe concentration and type of carrier fluid, whereas the other parameters did not contribute significantly. The authors showed that 32 vol% of 300 mesh Fe dispersed in Mi with 0.5 vol% of OA and 0.7 vol% of TMAH gave an optimized MRF with a τ y of 48.07 kPa (experimentally) and 48.197 kPa (theoretically) at 1 T. A similar approach of using orthogonal array was used by Zuzhi et al, [ 79 ] finding that low stirring temperatures, high stirring speeds, and a short first stirring time before a long second stirring time increased sedimentation stability.…”
Section: Ci‐based Mrfsmentioning
confidence: 96%
“…This could be due to better particle chain formation and higher MR effect in lower viscosity oil. Also, base oil having low viscosity results in quicker response time and easier redispersibility of particles (Zuzhi et al, 2016). Also, the difference in torque values obtained for 50 cSt and 100 cSt based MRFs increases with increase in current supplied.…”
Section: Selection Of Optimal Composition Of Mrfmentioning
confidence: 99%
“…MF75M50 fluid has lowest stability as it contains lower base oil viscosity and larger particle size of iron powder in MRF. However, a lower oil viscosity causes faster response time of MRF and better redispersibility of iron particles after the particles have settled (Zuzhi et al, 2016). MRFs having SSIP have lower slope compared to MSIP based MRFs and takes more time to completely settle indicating higher sedimentation stability of SSIP based MRFs.…”
Section: Selection Of Optimal Composition Of Mrfmentioning
confidence: 99%
“…The off-state viscosity of MRF should be as low as possible to reduce the off-state forces and hence increase the dynamic range of the MR damper. Also, a lower viscosity causes a faster response time of MRF and better redispersibility of iron particles [24]. Fumed silica (Sigma-Aldrich) and aluminium distearate (Sigma-Aldrich) with 3% of mass of base fluid were used as additives during the preparation of all the six MRF samples.…”
Section: Synthesis Of Magnetorheological Fluidmentioning
confidence: 99%